Educational visit to Bank Negara Malaysia: bridging theory and practice in financial education - Mejri, Norazimah (Corporate Communication Unit, UiTM Mukah Campus, 2025)
Students also explored BNM’s key initiatives, such as Financial Education Network (FEN) and the Financial Sector Blueprint, which aim to improve financial literacy and develop a resilient financial ecosystem. The visit included a tour of the Bank Negara Malaysia Museum and Art Gallery, where students learned about the history of currency in Malaysia, financial systems, and the role of central banking in national development. One of the highlights was an interactive simulation that allowed students to take on roles as central bankers, making decisions on interest rates based on economic scenarios.